Fatigue and apathy in patients on chronic hemodialysis. Issue 5 (5th January 2022) - Bossola, Maurizio; Di Stasio, Enrico; Monteburini, Tania; Santarelli, Stefano; Cenerelli, Stefano; Manes, Massimo; Parodi, Emanuele Luigi; Angioletti, Laura; Balconi, Michela
Abstract: Introduction: This study explores the link between fatigue and apathy in patients on chronic hemodialysis (HD). Methods: One hundred thirty‐nine chronic HD patients underwent the assessment of fatigue, apathy, depression, and their functional status, with the fatigue severity scale (FSS), the Apathy Evaluation Scale (AES), the beck depression inventory (BDI), the activity of daily living (ADL), and instrumental activity of daily living (IADL). Results: Patients with high FSS had a significantly lower ADL and IADL score, higher BDI, Charlson Comorbidity Index, and AES score, and lower serum levels of creatinine, compared to low FSS patients. FSS was highly correlated with the AES, as well as with the BDI and the AES correlates with the BDI. At multiple regression analyses, only apathy and IADL were independent predictor variables of fatigue in HD population. Conclusion: Future longitudinal studies could determine if apathy is a causative factor for fatigue manifestation and development in HD patients.